2001
DOI: 10.1097/00000542-200111000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Pharyngeal Function and Airway Protection During Subhypnotic Concentrations of Propofol, Isoflurane, and Sevoflurane

Abstract: Subhypnotic concentrations of propofol, isoflurane, and sevoflurane cause an increased incidence of pharyngeal dysfunction with penetration of bolus to the larynx. The effect on the pharyngeal contraction pattern was most pronounced in the propofol group, with markedly reduced contraction forces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(56 citation statements)
references
References 14 publications
1
52
0
2
Order By: Relevance
“…One such study examined airway protection at subhypnotic doses of anesthetics and found that all anesthetics tested compromised pharyngeal function. Furthermore, propofol had the greatest effect upon pharyngeal contraction pattern, 91 a finding that agrees with the animal study. 89 Another clinical trial 92 suggests that ketamine has similar protective effects on ventilatory drive as that observed in preclinical trials.…”
Section: Educationsupporting
confidence: 88%
“…One such study examined airway protection at subhypnotic doses of anesthetics and found that all anesthetics tested compromised pharyngeal function. Furthermore, propofol had the greatest effect upon pharyngeal contraction pattern, 91 a finding that agrees with the animal study. 89 Another clinical trial 92 suggests that ketamine has similar protective effects on ventilatory drive as that observed in preclinical trials.…”
Section: Educationsupporting
confidence: 88%
“…Propofol in rats is more respiratory depressant than isoflurane given at equianalgesic doses, which seems to be similar in humans, during anesthesia, 44 and during sedation under spontaneous ventilation. 45 If our results obtained in rats translate to the clinical situation of patients scheduled to undergo surgery, then the choice of the anesthetic agent might influence the safety of patients with airways unprotected by an endotracheal tube or a laryngeal mask, during conscious sedation, 43,46 or in extubated patients recovering from general anesthesia. 47 The strong impairing effects of propofol on upper airway dilator muscle function were reversed by carbon dioxide administration, which increased respiratory drive.…”
Section: Possible Clinical Implicationsmentioning
confidence: 96%
“…Some studies in humans suggest that subhypnotic concentrations of propofol have stronger decreasing effects on upper esophageal sphincter resting tone than isoflurane, 43 whereas other data suggest the opposite. 7,8 To our knowledge, it is unclear what the effects of equianesthetic concentrations of propofol and isoflurane on upper airway dilator muscle function might be.…”
Section: Possible Clinical Implicationsmentioning
confidence: 99%
“…In the last few years, several anaesthetic protocols combining propofol for its depression of laryngeal reflexes (Sundman et al 2001) with various doses of opioids have attempted to challenge the quality of intubation provided by muscle relaxants. Nevertheless, laryngoscopy and tracheal intubation create very intense but brief noxious stimuli and therefore call for a very deep level of analgesia to be maintained only for a short duration.…”
Section: Induction and Airway Controlmentioning
confidence: 99%